A nine-test screening battery for athletes: a reliability study - Frohm, A.; Heijne, A.; Kowalski, J.; Svensson, P.; Myklebust, G. (Scandinavian Journal of Medicine & Science in Sports, 2012)
Studies have shown that reduced neuromuscular control or strength increases the risk of acute injuries. It is hypothesized that a non-functional movement pattern can predispose for injuries. In the present paper a detailed description of a test battery consisting of nine different tests to screen athletic movement pattern is provided. The aim was to evaluate the inter- and intra-rater reliability of the test battery on a group of male elite soccer players. Twenty-six healthy elite soccer players (17-28 years) were screened. Eighteen participated at a second occasion 7 days later. No significant difference (P=0.31) was found between test occasion 1 (LS means 18.3, 95% confidence interval 14.9-21.7) and test occasion 2 (18.0, 14.4-21.7) in the mean total score of the test battery. No significant difference in the inter-rater reliability was found between the eight physiotherapists at the two test occasions. The intra-class correlation coefficient was 0.80 and 0.81, respectively. The test battery showed good inter- and intra-rater reliability. The screening battery is easy to use for familiarized professionals and requires minimal equipment. However, further studies are needed to confirm the validity of the test battery in injury prevention, rehabilitation and performance enhancement.